Peer effects at work on parental leave: Why is Papa not more involved? - Yaya Diallo; Fabian Lange (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2025)
We use the 2006 Qu'ebec paternity leave reform to replicate Dahl et al., 2014 who estimate the peer effects of paternity leave taking among male co-workers. The Qu'ebec reform of the paternity leave system closely resembles the Norwegian 1993 reform they analyze. Using high-quality administrative data, we follow their birth-date regression discontinuity research design as closely as possible. Depending on the length of follow-up, we estimate that having a male co-worker take paternity leave increases the probability that a father of a new-born takes leave by 3-6 percentage points. These estimates are, however, imprecise and are therefore consistent with the 11 percentage point increase reported by Dahl et al., 2014. Crudely combining estimates from both papers suggests an effect size of 7.8 percentage points and a standard error of 3.4 percentage points.
Keywords: 330